Physical and chemical analysis of Beirut ammonium nitrate blast: A concern of particulate matter in atmosphere (Nepal Journal of Environmental Science, 2022)
Chemical disasters are caused by improper management, handling, transportation, and sudden accidents. The massive explosion of ammonium nitrate silo in the port of  Beirut on August 4, 2020, has threatened the world with the loss of 220 people, about 6500 injuries,  huge property loss, and environmental contamination. This paper aims to summarize the major ammonium nitrate accidents in the past 100 years in the world. We analyzed the accidents in terms of frequency, causes, property loss, and deaths. We reported 43 accidents in which 7 accidents triggered more than 100 casualties. Altogether seven terrorist attacks with ammonium nitrate are reported leading to the death of 411 people and huge loss of assets. The explosion releases a large amount of energy and produces a variety of gases along with nitrogen oxides, ammonia,  and a lot of particulate matter (PM), which significantly contributes to air pollution. The size and amount of  PM imposes negative impact on environment like low visibility, decreased solar radiation and adverse health impacts like chronic respiratory, pulmonary, cardiovascular, and other human diseases. Proper management and safety measures with stringent regulations at national and international level is warranted for the safe and sustainable use of industrial chemicals.